A kind of Co-based coordination compounds with tunable morphologies and its Li-storage mechanism. (1st August 2022) - Lu, Yifei; Yuan, Libo; Peng, Qianqian; Qi, Shuo; Wang, Lei; Chen, Jiaxin; Wang, Yiting; Lv, Li-Ping; Sun, Weiwei; Wang, Yong; Chen, Shuangqiang
Highlights: Co-PG-2 with flower structure was obtained by adjusting the reaction ratio of raw materials. The Co-PG-2 exhibited outstanding lithium storage capabilities. The lithium storage mechanism (relating to C=O, C=C, and Co 2+ ) of Co-PG-2 is confirmed by ex-situ XPS, in-situ XRD and in-situ FTIR. Abstract: The metal-organic coordination compounds have shown great potential in lithium-ion batteries (LIBs) because of the moderate preparation conditions, high specific surface area, and diverse topological structures. Herein, a kind of Co-based coordination compounds with tunable morphologies are synthesized via a microwave-assisted solvothermal method by adjusting the molecular ratios between cobalt salts and phloroglucinol (PG) (Co-PG-x, x = 1, 2 and 3) for LIBs anode. Among them, Co-PG-2 with a unique flower structure, composed of ultra-thin flakes, has exhibited the most active sites (C=O, C=C groups of benzene ring and Co 2+ ) and the highest specific surface areas. When applied as the anode of LIBs, Co-PG-2 has displayed excellent cycle stability (a high reversible capacity of 752 mAh g −1 at 1 A g −1 after 500 cycles) and an outstanding rate performance (up to 5 A g −1 ). Moreover, practical application is demonstrated by the full cells, composed of Co-PG-2 electrode and when paired with LiFePO4 in the full cells, it delivers a reversible capacity of 85 mAh g −1 at 0.2 A g −1 after 50 cycles. In a word, these Co-based coordination compounds have exhibited extraordinary prospects for renewable organic materials applied in lithium storage.